Is theology a science? the nature of the scientific enterprise in the scientific theology of Thomas Forsyth Torrance and the anarchic epistemology of Paul Feyerabend - Munchin, David. (Studies in Systematic Theology, 2011)
When Barth and Scholz clashed over the scientific status of theology, Barth drew the conclusion that if natural science was to be drawn up in such positivistic terms, theology had much to lose and little to gain by engagement with it. A generation later Barth's translator and pupil Thomas Torrance maintained that science had changed enough to make an engagement more fruitful. In works such as Theological Science , Torrance sketched out the contours of such and engagement. However at the same time the anarchic philosopher of science, Paul Feyerabend, in books such as Against Method , sought to deconstruct any notion of 'science' as ultimately the protection of vested interests. This book analyses whether Torrance's notion of science can withstand this newer post-modern threat.